Alumni spot - Enríquez, Dharma (El Outsider: Journal of International Relations and Political Science, 2025)
The Alumni Spot features interviews with prominent alumni from the International Relations and Political Science programs at the Universidad San Francisco de Quito. Four students who continue to thrive in their professional lives. They share their journey through university and offer advice for all International Relations and Political Science students.